2020
DOI: 10.5430/ijhe.v10n2p240
|View full text |Cite
|
Sign up to set email alerts
|

Gender Inequality, Stress Exposure, and Well-Being among Academic Faculty

Abstract: Gender inequalities in salary, rank and access to leadership positions characterize institutions of higher education and disadvantage women faculty. Differential exposure to noxious working conditions and restricted access to social resources may underlie these inequalities by detracting from women faculty’s well-being, thereby perpetuating the status quo. This study applies stress process theory to analyze this inequitable state of affairs, treating gender as a social status in higher education that predicts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 51 publications
0
9
0
5
Order By: Relevance
“…Other obstacles identified in the same study are a lack of mentors, a lack of balance between work and family responsibilities, lack of faculty status, safety concerns when traveling independently, and limited networking opportunities due to not fitting in the “old boys’ club.” An added challenge for women specific to international education is “the stigma of international work” as it is viewed as “frivolous” and not strategically important (Gaudette et al, 2018, p. 18). A study of faculty at one U.S. university (M. Elliott & Blithe, 2021) reported that female academics faced more micro-aggressions and work-life conflicts and experienced a lower level of dean support than male faculty.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Other obstacles identified in the same study are a lack of mentors, a lack of balance between work and family responsibilities, lack of faculty status, safety concerns when traveling independently, and limited networking opportunities due to not fitting in the “old boys’ club.” An added challenge for women specific to international education is “the stigma of international work” as it is viewed as “frivolous” and not strategically important (Gaudette et al, 2018, p. 18). A study of faculty at one U.S. university (M. Elliott & Blithe, 2021) reported that female academics faced more micro-aggressions and work-life conflicts and experienced a lower level of dean support than male faculty.…”
Section: Literature Reviewmentioning
confidence: 99%
“…An added challenge for women specific to international education is "the stigma of international work" as it is viewed as "frivolous" and not strategically important (Gaudette et al, 2018, p. 18). A study of faculty at one U.S. university (M. Elliott & Blithe, 2021) reported that female academics faced more micro-aggressions and work-life conflicts and experienced a lower level of dean support than male faculty. Such negative experiences were also associated with a higher level of stress and lower job satisfaction in female faculty.…”
Section: Barriers For Women's Professional Advancementmentioning
confidence: 99%
“…Dazu zählen unter anderem Nachwuchswissenschaftlerinnen und Nachwuchswissenschaftler (Levecque et al, 2017), die während der Promotion ein hohes Maß an negativen Emotionen, Stress und Erschöpfung erleben, die ihr SWB vermindern können (Stubb et al, 2011). Weitere Studien belegen, dass das Hochschulsystem Frauen benachteiligt, was deren Zufriedenheit und damit auch ihr Wohlbefinden im Beruf vermindert (Elliott & Blithe, 2020). So wird erfahren, dass eine akademische Karriere und Verantwortlichkeiten für die Familie immer noch schwierig zu vereinbaren sind (Elliott & Blithe, 2020).…”
Section: Subjektives Wohlbefinden Von Hochschuldozierendenunclassified
“…Weitere Studien belegen, dass das Hochschulsystem Frauen benachteiligt, was deren Zufriedenheit und damit auch ihr Wohlbefinden im Beruf vermindert (Elliott & Blithe, 2020). So wird erfahren, dass eine akademische Karriere und Verantwortlichkeiten für die Familie immer noch schwierig zu vereinbaren sind (Elliott & Blithe, 2020). Insgesamt zeigen sich die Ergebnisse von Studien zu geschlechtsspezifischen Unterschieden im SWB allerdings inkonsistent (vgl.…”
Section: Subjektives Wohlbefinden Von Hochschuldozierendenunclassified
See 1 more Smart Citation